Antimicrobial Susceptibility Patterns of Escherichia Coli From Various Clinical Sources - Gautam, R; Chapagain, ML; Acharya, A; Rayamajhi, N; Shrestha, S; Ansari, S; Upadhaya, G; Nepal, Hari Prasad (Journal of Chitwan Medical College, 2013)
Escherichia coli is the major organism causing the urinary tract infection, wound infection and respiratory tract infection. A total of 2376 samples of urine, wound swab and sputum were analyzed for identification of bacterial isolates and their antimicrobial susceptibility pattern. Escherichia coli (E. coli) was isolated from 357 [15%] samples. Majority of the E.coli, 307 [85.9%], were obtained from the urine samples, followed by wound swab [8.4%] and sputum [5.6%]. High degree of resistance was observed for nalidixic acid [92.8%] followed by ceftriaxone [65.7%] and cotrimoxazole [64.6%]. The isolates were highly sensitive to imipenem (100%) followed by nitrofurantoin [90.3%] and amikacin [82.1%]. Journal of Chitwan Medical College 2013; 3(1): 14-17 DOI: http://dx.doi.org/10.3126/jcmc.v3i1.8459